Symposium 3: International Mission Impossible? ICT and Alternative Approaches to Internationalising the Curriculum - Caruana, Viv (Proceedings of the International Conference on Networked Learning, 2004)
Whilst Higher Education Institutions (HEIs) increasingly define their competitive and developmental strategies in terms of an ‘international mission’ the concept, in practical terms remains ill-defined. Particular uncertainty surrounds the potential of information and communication technology (ICT) in supporting different conceptions of, and strategies for internationalization. The University of Salford’s (UoS) international mission provides a starting point for considering the rationales underpinning internationalization and the range of approaches which may be deployed in embedding an international dimension in the curriculum. The paper goes on to gauge the ways in which institutions are aware of and act upon internationalization in a strategic way; to investigate the dominant approaches to internationalization and suggest how ITC may be deployed as part of an internationalized learning, teaching and assessment strategy.